New age in Latin America : popular variations and ethnic appropriations - Torre, Renée de la.; Gutiérrez Zúñiga, Cristina.; Juárez Huet, Nahayeilli. (Religion in the Americas, 2016)
This book is at the crossroads where a New Age sensibility, advancing like an ecumen of worldwide spirituality without national, cultural, or ecclesiastical frontiers, meets Latin America's syncretic religions, practiced by groups of people wiht African or indigenous roots or developed from the tradition of popular Catholicism. The Syncretic character of the two sensibilities makes both the New Age and popular religion behave like two, syncretizing and syncreticizable matrices of meaning. This book opens up a rich vein of debate with new dilemmas and discussions, that will provide a framework for a new field of study in anthropology. What new ways of signifying living and experiencing religion is the New Age generating in Latin America? What are its limits?